Pattern-focused therapy : highly effective CBT practice in mental health and integrated care settings - Sperry, Len (New York : Routledge, 2020)
"Pattern-Focused Therapy incorporates brief cognitive behavioral therapy interventions for symptom reduction and a step-by-step therapeutic strategy for effectively changing clients' maladaptive patterns and increasing their well-being. Seasoned and beginner therapists alike will benefit from this invaluable method for learning and mastering this evidence-based approach"--
OCLC-licensed vendor bibliographic record.
Keywords: Cognitive therapy; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Mental Health